Photosensitive Bent Core Liquid Crystal for Optical Storage Devices - Avazpour, Mahrokh; Lutfor, M. R.; M. M., Yusoff; Hegde, Gurumurthy (2013)
The amount of information produced annually is exponential in growth. Currently available magneto-optical materials have reached their storage buffer due to physical limitations imposed by the superparamagnetic effect and will not be able to meet future storage requirements. The simple fact is that present optical storage technology suffers from an absence of functional organic materials that apply to the next generation of commercially available laser diodes (Nichia blue lasers, 400 - 500 nm). Although 'Blu-Ray' DVD technology has arrived with storage capacities ranging from 27-54 GB(operating at 405 nm with 0.85NA), the materials are still to be optimised. Higher storage densities of up to 80 GB may be achieved by depositing several layers of a material which is not ideal due to loss of resolution. An ideal material is yet to be realised. In addition, the future will demand a shift to even shorter wavelengths such as UV so that even higher capacities may be managed. Moreover cost is the main area of concern and it is necessary to further develop the materials in this direction. In recent years, a field of research that is growing steadily is that of photo induced phenomenon, in which the incident light itself brings about molecular ordering/ disordering of the liquid- crystalline system. This particular aspect of photonics, in which light can be controlled by light as a stimulus, is being proposed as the future technology for high-speed information processing [1-2]. Azobenzene undergoes trans → cis isomerization when irradiated with light tuned to an appropriate wavelength. The reverse cis → trans isomerization can be driven by light or occurs thermally in the dark. Azobenzene's photochromatic properties make it an ideal component of numerous molecular devices and functional materials. Despite the abundance of application-driven research, azobenzene photochemistry and the isomerization mechanism remain topics of investigation[3]. In this report photoisomerization studies were performed on in house prepared anisotropic molecule exhibiting bent core system. It is showing liquid crystalline phases, namely nematic and smectic phase. The photo-switching property of bent core was investigated in chloroform using UV/visible spectroscopy in the absence and in the presence of UV light illumination with 365 nm wavelength passing through heat filter to avoid possible heat raditation which might cause the changes in the system. Compound was illuminated which leads to the E isomer being transformed into the Z isomer. After ∼20 s illumination, there is no change in the absorption spectrum which confirms the photosaturation of the E/Z isomerization process, The reverse transformation from Z to E can be brought by two methods, one by keeping the solution in dark and other by shining white light of higher wavelength. The earlier process is well known as thermal back relaxation.